Perception of fall risk in hospitalized patients and associated factors: A cross-sectional study and path analysis - Ye Luo; Yuanfei Liu; Suxian Tan; Tian Xu; Guanjun Bao (SAGE Open Medicine)
Background and purposes: Evidence regarding patients’ perception of fall risk is scarce. This study aimed to investigate the current situation and the associated factors of patients’ perception of fall risk, explore the mechanisms, and identify the subgroup of patients who may be at greater risk of having an erroneous perception. Methods: Participants were recruited from three wards of two tertiary general hospitals in China. Three-step multiple linear regression analyses were conducted including the demographic characteristics, health status factors, and fall-related factors as independent variables and Fall Risk Perception Questionnaire scores as dependent variable. The interactions of age, gender, and ward with fall-related factors were explored to test the potential moderating effects. We also examined the mediating role of fear of falling in the relationship of previous falls and age and perception of fall risk. Results: Patients who were in their older age, female, from endocrinology ward, had comorbidities, ambulatory aids, and fear of falling demonstrated a higher perception of fall risk which may or may not align with their actual risk of fall. The impact of previous fall injuries on perception of fall risk was significantly higher in older adults. The effects of fall-related training on patients’ perception of fall risk varied across wards. The fear of falling is a significant mediator between age and perception of fall risk. Conclusion: By understanding the self-perception of fall risk, health professionals would identify the population at higher risk of having an erroneous perception of their fall risk. This study increases health professional’s awareness and informs administrators to design and implement effective intervention and strategies that target patients’ perception of fall risk to promote patient safety.